Needs Assessment To Develop A Vocational Identity Crisis Instrument For Students - Yunita Odinlia Ere; Henny Indreswari; Khairul Bariyyah (UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to analyze the need for developing a vocational identity crisis instrument for university students, as a first step to address the lack of contextually relevant career crisis assessment tools in Indonesia. This descriptive quantitative study involved 30 fourth- and sixth-semester students from the Catholic Religious Education program at Atma Reksa Pastoral College in Ende, selected using a purposive sampling technique. The initial instrument was developed based on five aspects: career confusion, self-doubt, lack of direction in life, difficulty in decision-making, and emotional response, consisting of 30 statements with a four-point Likert scale. Content validity was evaluated by three experts, resulting in Aiken's V coefficients ranging from 0.73 to 0.92. Descriptive statistics showed that all dimensions were in the moderate category, with mean scores ranging from 2.69 to 2.87. The lack of direction in life dimension was the most prominent (M=2.87; SD=0.39), followed by the emotional response dimension (M=2.85; SD=0.44). These findings reveal that university students experience psychosocial vulnerability, highlighting the urgent need for preventive career planning support. Implicitly, the 30 developed statements effectively reflect the actual conditions of students and provide a strong empirical foundation for further validity and reliability testing in scale development. Future research should expand the sample size and conduct Confirmatory Factor Analysis (CFA).